Tillage and N-source affect soil fertility, enzymatic activity, and crop yield in a maize–rice rotation system in the Indian Terai zone - Sahoo, Samaresh; Mukhopadhyay, Prabir; Mowrer, Jake; Maity, Pragati Pramanik; Maity, Aniruddha; Sinha, A.K.; Sow, Prodipto; Rakesh, S (Frontiers in Environmental Science, 2022)
A field experiment (2017-2019) was undertaken to study the short-term effects of tillage [zero tillage (ZT), conventional tillage (CT), & alternate tillage (AT)], and sources of organic and mineral fertilizer N [NS0 –control; NS1 – recommended doses of fertilizer (160:50:100); NS2 – recommended level of fertilizer and crop residue (6 Mg ha-1); NS3 – 75% of recommended N as fertilizer (120 kg ha⁻¹) and 25% N (40 kg ha⁻¹) as farm yard manure (FYM) and NS4 – 75% of recommended N as fertilizer and 25% N as vermicompost] on yield and soil quality under a maize-rice rotation system. Among N sources, NS4 produced the highest maize grain yield (10 Mg ha⁻¹). Residual effects of N sources on mean rice grain yield were evident only in crop residue (NS2) and vermicompost (NS4) treated plots. After the harvest of two complete maize-rice crop cycles, higher content of dehydrogenase activity (DHA) and urase activity (UR) were observed in soil under AT as compared to ZT and CT at 0-10 cm (P<0.05). Similarly, microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) also recorded positive changes at 0-10 cm soil depth, especially in NS2 and NS4 treatments. AT resulted in highest total soil carbon (TOC) (8.10 g kg-1), followed by CT (6.73 g kg-1) and ZT (5.98 g kg-1). Fertilizer N treatments, however, influenced the NO3-N accumulation beyond the root zone, where crop residue based (NS2) fertilizer N treatment resulted in highest NO3-N (32.52 kg ha-1) and lowest NO3-N (14.48 kg ha-1) was observed in FYM based (NS3) treatment. Therefore, the practice of alternate tillage and integration of vermicompost (40 kg N ha-1) and chemical fertilizer (total 120 kg ha-1) sources should be most recommended to farmers in Terai region, India.